Advances in Research on the Regulatory Roles of lncRNAs in Osteoarthritic Cartilage - Jiaqi Wu; Zhan Zhang; Xun Ma; Xueyong Liu (Biomolecules, 2023)
Osteoarthritis (OA) is the most common degenerative bone and joint disease that can lead to disability and severely affect the quality of life of patients. However, its etiology and pathogenesis remain unclear. It is currently believed that articular cartilage lesions are an important marker of the onset and development of osteoarthritis. Long noncoding RNAs (lncRNAs) are a class of multifunctional regulatory RNAs that are involved in various physiological functions. There are many differentially expressed lncRNAs between osteoarthritic and normal cartilage tissues that play multiple roles in the pathogenesis of OA. Here, we reviewed lncRNAs that have been reported to play regulatory roles in the pathological changes associated with osteoarthritic cartilage and their potential as biomarkers and a therapeutic target in OA to further elucidate the pathogenesis of OA and provide insights for the diagnosis and treatment of OA.